OPTN/SRTR 2020 Annual Data Report: Pancreas. (10th March 2022) - Kandaswamy, R.; Stock, P. G.; Miller, J.; White, J.; Booker, S. E.; Israni, A. K.; Snyder, J. J.
Abstract : The number of pancreas transplants decreased in 2020 to 962, compared with 1015 in 2019, at least partly due to the COVID‐19 pandemic. The number of simultaneous pancreas‐kidney (SPK) and pancreas transplant alone (PTA) transplants decreased by 5.2% and 12.1%, respectively, while pancreas after kidney transplants (PAKs) increased 9.1%. New waitlist registrations decreased to 1585 in 2020, compared with 1771 in 2019. The decrease in waitlist registrations was predominately driven by SPK and PAK, down by 11.7% and 16.9%, respectively. The proportion of type 2 diabetes patients on the waiting list increased to 20.1% in 2020, compared with 17.6% in 2019. Waiting times increased in SPK and PTA, with last calculated median months to transplant at 14.1 months for SPK (up from 12.3 months) and 42.4 months for PTA (up from 22.3 months). Data on 1‐year transplant graft failure, published for the first time in about a decade, show that for transplants performed in 2019, graft failure rates were 6.9% for SPK, 10.3% for PTA, and 6.8% for PAK, compared with 9.5% for SPK, 7.6% for PTA, and 16.2% for PAK for transplants performed in 2018. Other short‐ and long‐term outcomes, including patient survival, kidney graft survival, and acute rejection‐free survival, continued to show consistent improvement over the past decade.